2007
DOI: 10.1016/j.atherosclerosis.2006.05.024
|View full text |Cite
|
Sign up to set email alerts
|

High interleukin-6 plasma levels are associated with low HDL-C levels in community-dwelling older adults: The InChianti study

Abstract: Background-Low levels of high density lipoprotein cholesterol (HDL-C) are associated with increased incidence of coronary heart disease (CHD). A better understanding of the mechanisms leading to low HDL-C and CHD is essential for planning treatment strategies. Clinical studies have demonstrated that cytokines might affect both concentration and composition of plasma lipoproteins, including HDLs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
42
0
5

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(53 citation statements)
references
References 38 publications
6
42
0
5
Order By: Relevance
“…As mentioned in the introduction, inflammation (induced by endotoxin administration) has been reported to be a negative regulator or suppressor of HDL-C levels (Hardardottir et al, 1994;Volpato, Palmieri, Fellin, & Zuliani, 2000;Zuliani et al, 2007). There is also an epidemiological report showing that higher levels of pro-inflammatory IL-6 were associated with lower levels of HDL-C in older adults (Zuliani et al, 2007). Additionally, pro-inflammatory cytokines, such as IFN-g, TNF-a and IL-1b impair reverse cholesterol transport, in which HDL is one of the major constituents (Ohashi, Mu, Wang, Yao, & Chen, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned in the introduction, inflammation (induced by endotoxin administration) has been reported to be a negative regulator or suppressor of HDL-C levels (Hardardottir et al, 1994;Volpato, Palmieri, Fellin, & Zuliani, 2000;Zuliani et al, 2007). There is also an epidemiological report showing that higher levels of pro-inflammatory IL-6 were associated with lower levels of HDL-C in older adults (Zuliani et al, 2007). Additionally, pro-inflammatory cytokines, such as IFN-g, TNF-a and IL-1b impair reverse cholesterol transport, in which HDL is one of the major constituents (Ohashi, Mu, Wang, Yao, & Chen, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…It has also been reported that Se supplementation protects LDL from oxidation and other atherogenic changes [33,34]. HDL possesses anti-atherogenic activity [35] and has been found to protect against the oxidation of LDL by metal ions in vitro [36,37] and by reverse cholesterol transport [38]. In the present study, total cholesterol (P<0.001), triglycerides (P<0.05), and HDL (P<0.05) levels were found to be significantly increased in HCD group in comparison to the control group.…”
Section: Resultsmentioning
confidence: 96%
“…Several authors have suggested that IL6 with other pro-inflammatory cytokines can influence HDLc levels of by modifying the triglycerides lipase activity [34].…”
Section: Discussionmentioning
confidence: 99%